Anchoring Active Sites by Pt2FeNi Alloy Nanoparticles on NiFe Layered Double Hydroxides for Efficient Electrocatalytic Oxygen Evolution Reaction. Issue 1 (8th April 2021) - Zheng, Zhicheng; Guo, Yanru; Wan, Hao; Chen, Gen; Zhang, Ning; Ma, Wei; Liu, Xiaohe; Liang, Shuquan; Ma, Renzhi
Abstract : Strategy of anchoring alloy nanoparticles made up of the efficient catalytic element (e.g., Ni, Fe) on dodecyl sulfate (DS ‐ )‐intercalated NiFe layered double hydroxides (DS ‐ ‐NiFe LDH) obtained by a convenient one‐step hydrothermal coprecipitation method for essentially enhancing oxygen evolution reaction (OER) performance was proposed. The results of structural characterization indicate Pt2 FeNi alloy nanoparticles evenly distribute on the surface of DS ‐ ‐NiFe LDH. The sizes of the Pt2 FeNi nanoparticles, closely related to their OER performance, could be well‐controlled by adjusting the amount of H2 PtCl6 addition. The composite structure of as‐prepared product was stable during processes of synthesis, exfoliation, self‐assembly, and subsequent electrocatalytic OER. Rigorous electrochemical test proving the contributing catalytic active sites was located at the interface between Pt2 FeNi and DS ‐ ‐NiFe LDH, and the Ni and Fe were the major active elements while O atoms are adsorption sites. The formation of Pt2 FeNi nanoparticles could greatly prompt the reduction of Tafel slope. The best‐performing Pt2 FeNi/DS ‐ ‐NiFe LDH with a Pt content of 0.98 wt% achieved low overpotential of 204 mV at 10 mA cm −2 and 262 mV at 50 mA cm −2 . This work provides a convenient and effective strategy to create additional active sites for enhancing OER performance of NiFe LDH and make contribution to its wide application. Abstract : A stable composite comprising Pt2 FeNi nanoparticles and NiFe LDH was prepared as an excellent electrocatalyst for oxygen evolution. The characterization results indicated that the active atoms (e.g., Ni, Fe) in the Pt2 FeNi nanoparticles were bond with NiFe LDH tightly, contributing to significantly improved electrocatalytic performance due to the interfacial effect